Gambaran Kecemasan Keluarga Pasien Gangguan Jiwa Saat Menemani Pasien Rawat Jalan di Rumah Sakit Jiwa - Rahmi Dwi Yanti; Salvita Fitrianti (Prosiding Seminar Kesehatan Nasional, 2022)
The impact of the COVID-19 outbreak has had a profound effect on the whole world, and Indonesia in general. This virus is related to various aspects, including in terms of human mental health. The Jambi Province Mental Hospital (RSJ) receives hundreds of patients every day who consult their mental conditions, not a few of whom complain of anxiety and worry about the impact of the Covid-19 pandemic outbreak. Mental health is influenced by limited access to daily activities, social relationships. The occurrence of this epidemic is not only related to the risk of death, but is also related to the psychological pressure of the community. This study uses a quantitative descriptive research methodology. This study aims to describe the family anxiety of mental patients when accompanying outpatients at the Jambi Provincial Mental Hospital during the COVID-19 pandemic. The population and sample in this study were families of mental patients when accompanying outpatients at the Jambi Province Mental Hospital. The research sample was taken using the acidental sampling technique, and data collection was carried out using the HARS (Hamilton Anxiety Rating Scale) instrument. Data analysis with univariate analysis. The results showed that the level of anxiety of the family of mental patients when accompanying outpatients at the Jambi Provincial Mental Hospital during the COVID-19 pandemic, which varied from not anxious to moderate anxiety. The majority of respondents experienced mild anxiety, namely 40 people with a percentage of 53.3%. It is hoped that the results of this study will be used as input and consideration for the Jambi General Hospital, especially the outpatient polyclinic, in order to further improve health education activities and counseling to patients and their families in an effort to motivate families to treatment of mental patients..